2016
DOI: 10.1007/s40265-016-0542-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for Fragile X Syndrome: Progress to Date

Abstract: To date, no drug is approved for the treatment of Fragile X Syndrome (FXS) although many drugs are used to manage challenging behaviors from a symptomatic perspective in this population. While our understanding of FXS pathophysiology is expanding, efforts to devise targeted FXS-specific treatments have had limited success in placebo-controlled trials. Compounds aimed at rectifying excessive glutamate and deficient gamma-aminobutyric acid (GABA) neurotransmission, as well as other signaling pathways known to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 149 publications
0
29
0
Order By: Relevance
“…In Fmr1 knockout (KO) mice, the glutamatergic receptors signalling and/or localization is enhanced. New studies that try to reduce excitatory neurotransmission by antagonism of group I metabotropic glutamate receptors (mGluRs), particularly mGluR5, are still underway [93]. By now, studies conducted on Fmr1 KO mice demonstrated that the reduction of mGluR5 levels can normalize protein synthesis, dendritic spines, and some behaviour [94].…”
Section: Discussionmentioning
confidence: 99%
“…In Fmr1 knockout (KO) mice, the glutamatergic receptors signalling and/or localization is enhanced. New studies that try to reduce excitatory neurotransmission by antagonism of group I metabotropic glutamate receptors (mGluRs), particularly mGluR5, are still underway [93]. By now, studies conducted on Fmr1 KO mice demonstrated that the reduction of mGluR5 levels can normalize protein synthesis, dendritic spines, and some behaviour [94].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the existence of rare unmethylated full mutation individuals [122], suggests that pharmacologically restoring FMR1 transcription may be possible. …”
Section: Therapeutic Strategies In Fxsmentioning
confidence: 99%
“…Studies report that drugs used to treat excessive glutamate and insufficient γ-aminobutyric acid (GABA), signaling pathways affected by FMRP, are under different stages of development in FXS [15]. Thus, it is interesting to know whether the imbalance between excitatory and inhibitory circuitry is caused by a lack of astrocytic FMRP.…”
Section: Introductionmentioning
confidence: 99%